HTTP service based Network Intrusion Detection System in Cloud Computing - Lenka, Sudhansu Ranjan; Rath, Bikram Keshari (International Journal of Computer Sciences and Engineering, 2025)
Recently, the usages of Cloud Computing are increasing rapidly and gained tremendous success over the internet. Therefore, security is the major challenge in Cloud computing and one of the major issues is to protect the Cloud resources and the services against network intrusions. So Network Intrusion Detection System (NIDS) are installed in the Cloud networks to detect the intrusions in the system. In this paper we proposed an NIDS based on Naïve Bayes Classifier to be implemented in Cloud. The main aim of the NIDS is to improve the performance by preparing the training dataset which can detect the malicious connections that exploit the Cloud HTTP services. In the training phase, the Naïve Bayes Classifiers select the important Network traffic that can be used to detect the attacks. In the testing and execution phases the proposed IDS using the Naïve Bayes Classifier classifies the services based on the selected features into normal or attacks. The proposed IDS carried out on NSL-KDD’99 dataset and results in high detection with low false alarm as compared with other similar IDS.